A Mini Review of Antibacterial Activities of Uncaria gambir Roxb. - Satria, S.Si., M.Eng., Ph.D., Dedi (Department of Pharmacy, Muhammmadiyah University of Sumatera Barat, 2021)
Uncaria gambir Roxb., commonly known as Gambir, is a traditional medicinal plant widely used in Southeast Asia for its therapeutic properties. This mini-review aims to summarize the current understanding of the antibacterial activities of Uncaria gambir Roxb., with a focus on its potential as a natural alternative to synthetic antibiotics